REKONSTRUKSI KONSEP INOVASI PENDIDIKAN ISLAM BERBASIS DESIGN THINKING DAN NILAI ISLAMI - Imam Safi’i; Abdullah Syakur (Universitas Islam Bunga Bangsa Cirebon, 2023)
This study examines the reconstruction of Islamic education innovation concepts through the integration of Design Thinking methodology and Islamic values, addressing a critical gap in contemporary Islamic educational management discourse. The urgency of this research stems from the observed inadequacy of existing innovation frameworks in Islamic educational institutions, which tend to adopt secular innovation models without sufficient epistemological grounding in Islamic principles. This study aims to: (1) analyze the conceptual foundations of innovation in Islamic education, (2) examine Design Thinking as a problem-solving framework applicable to Islamic educational contexts, and (3) formulate a reconstructed model of Islamic education innovation that synthesizes Design Thinking stages with Islamic value systems. Employing a systematic library research methodology, this study critically reviewed thirty peer-reviewed sources spanning 2020 to 2025. The findings demonstrate that Design Thinking's five stages — empathize, define, ideate, prototype, and test — can be meaningfully reinterpreted through Islamic epistemological lenses, producing an integrated framework termed Islami Design Thinking for Education (IDTE). This model offers transformative implications for madrasah principals, Islamic school curriculum designers, and educational policymakers.